(untitled) (Boston, MA., 2004)
Life and death of microorganisms: Humans and the microbial world; Molecules of life; Microscopy and cell structure; Dynamics of prokaryotic growth; Control of microbial growth; Metabolism, fueling cell growth; Blueprint of life, from DNA to protein; Bacterial genetics; Biotechnology and recombinant DNA --- Microbial world: Identification and classification of prokaryotic organisms; Diversity of prokaryotic organisms; Eukaryotic members of the microbial world; Viruses of bacteria; Viruses, prions, and viroids, infectious agents of animals and plants -- Microorganisms and humans: Innate immune response; Adaptive immune response; Applications of immune responses; Immunologic disorders; Host-microbe interactions; Epidemiology; Antimicrobial medications -- Infectious diseases: Skin infections; Respiratory system infections; Alimentary system infections; Genitourinary infections; Nervous system infections; Wound infections; Blood and lymphatic infections; HIV disease and complications of immunodeficiency -- Applied microbiology: Microbial ecology; Environmental microbiology, treatment of water, wastes, and polluted habitats; Food microbiology -- Appendices: Microbial mathematics; Microbial terminology; Pronunciation key; Metabolic pathways; Answers to multiple choice questions -- Glossary
Keywords: Microbiology,Communicable diseases; Microbiology